High-Resolution Anoscopy or Expectant Management for Anal Intraepithelial Neoplasia for the Prevention of Anal Cancer: Is There Really a Difference?. Issue 1 (January 2015) - Crawshaw, Benjamin P.; Russ, Andrew J.; Stein, Sharon L.; Reynolds, Harry L.; Marderstein, Eric L.; Delaney, Conor P.; Champagne, Bradley J.
Abstract : BACKGROUND: High-resolution anoscopy has been shown to improve identification of anal intraepithelial neoplasia but a reduction in progression to anal squamous-cell cancer has not been substantiated when serial high-resolution anoscopy is compared with traditional expectant management. OBJECTIVE: The aim of this study was to compare high-resolution anoscopy versus expectant management for the surveillance of anal intraepithelial neoplasia and the prevention of anal cancer. DESIGN: This is a retrospective review of all patients who presented with anal squamous dysplasia, positive anal Pap smears, or anal squamous-cell cancer from 2007 to 2013. SETTING: This study was performed in the colorectal department of a university-affiliated, tertiary care hospital. PATIENTS: Included patients had biopsy-proven anal intraepithelial neoplasia from 2007 to 2013. INTERVENTIONS: Patients were treated with high-resolution anoscopy with ablation or standard anoscopy with ablation. Both groups were treated with imiquimod and followed every 6 months indefinitely. MAIN OUTCOME MEASURES: The incidence of anal squamous-cell cancer in each group was the primary end point. RESULTS: From 2007 to 2013, 424 patients with anal squamous dysplasia were seen in the clinic (high-resolution anoscopy, 220; expectant management, 204). Three patients (high-resolution anoscopy, 1; expectant management, 2) progressed to anal squamous-cell cancer; 2 were noncompliant with follow-up and with HIV treatment, and the third was allergic to imiquimod and refused to take topical 5-fluorouracil. The 5-year progression rate was 6.0% (95% CI, 1.5–24.6) for expectant management and 4.5% (95% CI, 0.7–30.8) for high-resolution anoscopy ( p = 0.37). LIMITATIONS: This was a retrospective review. There is potential for selection and referral bias. Because of the rarity of the outcome, the study may be underpowered. CONCLUSIONS: Patients with squamous-cell dysplasia followed with expectant management or high-resolution anoscopy rarely develop squamous-cell cancer if they are compliant with the protocol. The cost, morbidity, and value of high-resolution anoscopy should be further evaluated in lieu of these findings.